Out-of-home care in childhood and socio-economic functioning in adulthood: ONS Longitudinal study 1971–2011. (January 2022) - Sacker, Amanda; Lacey, Rebecca E.; Maughan, Barbara; Murray, Emily T.
Highlights: Socioeconomic, family and living arrangements in adulthood depend on care placement. Residential care predicted the worst outcomes, care by a relative the best. Differences were found in people's 20 s, 30 s and 40 s. Inequalities tended to widen not narrow from 1981 to 2011. Some returned to education later in life, with improvements to their circumstances. Abstract: Background: Children who spent time in non-parental care report poor outcomes in many aspects of their later lives on average, but less is known about differences by type of care. We examined whether socioeconomic, family, and living arrangements of adults who had been in non-parental care across the first three decades of adult life varied by type of care (residential, non-relative and relative). Methods: We used longitudinal data from the Office for National Statistics Longitudinal Study (LS). Participants were aged <18 years and had never been married at baseline of each census year from 1971 to 2001 (n = 242, 843). Separately for each adult follow-up age (20–29; 30–39; 40–49), multi-level logistic regression models were used to compare socioeconomic, family, and living arrangements by different out-of-home care (OHC) experiences. Results: Any OHC increased the likelihood of poorer functioning in the three domains of socioeconomic circumstances, family formation and relationships, and living arrangements. This was evident in participants' 20 s, 30 s and 40 s; the most adverse outcomes were observed for those with a history of residential care, followed by non-relative OHC, and the least adverse outcomes for relative OHC. Moderation by childhood census year and gender altered the relationship between OHC and some, but not all, adult outcomes. The strongest, most consistent, evidence was for widening of inequalities in outcomes across childhood census years. Conclusion: Enduring inequalities in social and economic functioning for OHC-experienced adults were found. The evidence supports the policy to place children in relative care whenever possible, with residential care the least favoured option.